Stand Together or Fall Alone:: Narratives from Former Teachers - Brante, Eva (Narrative Works, 2012)
In 2004 as many as 25% of teachers in Sweden, Denmark, and England were willing to leave their profession immediately; in the United States much effort has been invested in studying why teachers leave the profession. In this paper, four teachers who left the profession were interviewed from within the life- story tradition. In the narratives, which were rendered in a poetic style during the analysis, colleagues were mentioned both positively and negatively. The theme of having colleagues, and especially trust or mistrust between colleagues, was thus explored. The existence or nonexistence of lateral trust between teachers can be connected both to school development and to student learning outcomes.